International perspective on integrated care models in child and adult mental health. (17th February 2022) - Shaligram, Deepika; Skokauskas, Norbert; Aragones, Enric; Azeem, Muhammad Waqar; Bala, Abishek; Bernstein, Bettina; Cama, Shireen; Canessa, Laura; Silva, Flávio Dias; Engelhard, Caitlin; Garrido, Gabriela; Guerrero, Anthony P. S.; et al.
Abstract: The dearth of child and adolescent mental health services (CAMHS) is a global problem. Integrating CAMHS in primary care has been offered as a solution. We sampled integrated care perspectives from colleagues around the world. Our findings include various models of integrated care namely: the stepped care model in Australia; shared care in the United Kingdom (UK) and Spain; school-based collaborative care in Qatar, Singapore and the state of Texas in the US; collaborative care in Canada, Brazil, US, and Uruguay; coordinated care in the US; and, developing collaborative care models in low-resource settings, like Kenya and Micronesia. These findings provide insights into training initiatives necessary to build CAMHS workforce capacity using integrated care models, each with the ultimate goal of improving access to care. Despite variations and progress in implementing integrated care models internationally, common challenges exist: funding within complex healthcare systems, limited training mechanisms, and geopolitical/policy issues. Supportive healthcare policy, robust training initiatives, ongoing quality improvement and measurement of outcomes across programs would provide data-driven support for the expansion of integrated care and ensure its sustainability.